Hungry like the wolf: a word-pattern analysis of the language of psychopaths - Hancock, Jeffrey T. (Legal and criminological psychology, 2013)
Purpose. This study used statistical text analysis to examine the features of crime narratives provided by psychopathic homicide offenders. Psychopathic speech was predicted to reflect an instrumental/predatory world view, unique socioemotional needs, and a poverty of affect. Methods. Two text analysis tools were used to examine the crime narratives of 14 psychopathic and 38 non-psychopathic homicide offenders. Psychopathy was determined using the Psychopathy Checklist-Revised (PCL-R). The Wmatrix linguistic analysis tool (Rayson, 2008) was used to examine parts of speech and semantic content while the Dictionary of Affect and Language (DAL) tool (Whissell & Dewson, 1986) was used to examine the emotional characteristics of the narratives. Results. Psychopaths (relative to their counterparts) included more rational cause-and-effect descriptors (e.g., ‘because’, ‘since’), focused on material needs (food, drink, money), and contained fewer references to social needs (family, religion/spirituality). Psychopaths’ speech contained a higher frequency of disfluencies (‘uh’, ‘um’) indicating that describing such a powerful, ‘emotional’ event to another person was relatively difficult for them. Finally, psychopaths used more past tense and less present tense verbs in their narrative, indicating a greater psychological detachment from the incident, and their language was less emotionally intense and pleasant. Conclusions. These language differences, presumably beyond conscious control, support the notion that psychopaths operate on a primitive but rational level.